2016
DOI: 10.1021/acs.jpcc.5b12441
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Properties of Few-Layer Crystals of Quasi-One-Dimensional ZrS3 and ZrSe3

Abstract: The frequencies of Raman active modes of few-layer ZrS3 and ZrSe3 and their dependence on the number of layers have been investigated by Raman scattering spectroscopy and first-principles calculations. We find a considerable downshift of the frequency of the Ag 3 mode with decreasing the number of layers, and a slight downshift of the Ag 5 mode. The same frequency shifts are reproduced by the calculations with remarkable accuracy. We explain the difference in the frequency shifts of the Ag 3 and Ag 5 modes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…This is also observed in case of bulk nanobelts (Figure 2b). The enhancement in the intensity of the inplane vibrations (Eg and Eu) may be due to the extended interplanar spacing (as observed in TEM, Figure 3c) resulting in the oscillations of atoms more freely while decrease in intensity of out-of plane vibrations (A1g) can be attributed to dominating quantum confinement effects [39][40]. Further, it has been reported that the surface of HfS2 readily gets oxidized in presence of ambient oxygen increasing its thickness by 250 % due to the penetration of oxygen atoms inside the layers within a time span of 24 hours [22].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is also observed in case of bulk nanobelts (Figure 2b). The enhancement in the intensity of the inplane vibrations (Eg and Eu) may be due to the extended interplanar spacing (as observed in TEM, Figure 3c) resulting in the oscillations of atoms more freely while decrease in intensity of out-of plane vibrations (A1g) can be attributed to dominating quantum confinement effects [39][40]. Further, it has been reported that the surface of HfS2 readily gets oxidized in presence of ambient oxygen increasing its thickness by 250 % due to the penetration of oxygen atoms inside the layers within a time span of 24 hours [22].…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that A1g Raman mode is highly intense where as Eg and Eu (LO) modes are weak for standard hexagonal plates of HfS2 [22,38]. However, the enhancement of the in-plane vibrations modes Eg and Eu (LO) with a suppression of the out-of-plane vibrations (A1g) in case of nanobelts suggests quantum confinement effects [39][40] or change in the interlayer spacing between the multilayers of HfS2 in 1T-phase, which is well supported by our XRD results effecting Raman intensity. High resolution transmission electron microscopy (HRTEM) is also employed to calculate the distance between the atomic planes.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical exfoliation, using sticky tape or viscoelastic materials, has allowed exfoliation of individual nanoribbons down to a few layers. 53,140 The high aspect ratio of individual nanoribbons makes it challenging to isolate single layers. Recent calculations show that the interlayer potential (45 meV/atom), is less than that of MoS2 (60 meV/atom) and therefore should allow for exfoliation of the bulk down to a single layer.…”
Section: Isolation and Exfoliation Of Mx3 Crystalsmentioning
confidence: 99%
“…Osada et al investigated the phonon properties of few-layer quasi-1D form of ZrS 3 . 87 A considerable downshift of the frequency of the A 3 g mode with decreasing number of layers and a slight downshift of the A 5 g mode were found which were explained through intrachain, interchain, and interlayer force constants using simple 1D lattice models. Thus, it was pointed out that the large shift of the A 3 g mode reflects the quasi-1D structure of ZrS 3 .…”
Section: B Quasi-1d Behavior In Zrsmentioning
confidence: 88%